Multifunctional nanoarchitectured porous carbon for solar steam generation and supercapacitor applications. Issue 7 (8th March 2022) - Kumar, Nitish; Wani, Tawseef Ahmad; Pathak, Prakash Kumar; Bera, Ashok; Salunkhe, Rahul R.
Abstract : Multifunctional nanoporous carbon with high specific surface areas, tunable pore structures, good conductivity, and high optical absorption is a promising material for solar steam generation and supercapacitor applications. Abstract : Solar steam generation and supercapacitors are considered the best solutions for society's foremost issues such as wastewater treatment and energy storage. Nanoporous carbons derived from the metal–organic framework are of great interest for these applications because of their high specific surface areas, tunable pore structures, good conductivity, high optical absorption, and controllable shapes. To date, various nanostructures of carbons have been studied for solar steam generation and supercapacitors individually. This work portrays the simple synthesis of multifunctional nanoporous carbon for solar steam generation and electrochemical supercapacitor applications. The structural and surface area analysis confirms the formation of graphitic carbon with a high specific surface area of 321.4 m 2 g −1 . The polyhedron-shaped carbon-based solar absorber with a high absorption coefficient performs as a solar steam generator with an evaporation rate of 1.4 kg m −2 h −1 for 2D devices and 2.1 kg m −2 h −1 for the modified cone-shaped 3D devices under one sun illumination. Moreover, the symmetric two-electrode supercapacitor device for these materials in an ionic liquid electrolyte ([emim][BF4 ]/PC) demonstrates a maximum specific energy of 16.9 W h kg −1 and specific power of 10.9 kW kg −1 .